Legal Entities Entitled to Invoke International Responsibility - Krivenkova, Maria (Journal of History Culture and Art Research, 2018)
The paper is devoted to the consideration of one of the most pressing problems of invocation to international legal responsibility: the definition of the circle of subjects entitled to make claims against a violator of the norms of international law. Taking into account the existing mandatory and recommendatory norms of international law, as well as the existing practice of international judicial bodies, the paper emphasizes the need for a clear definition of the legal category "victim", since it is that which has the right to call an offender to justice. When determining a victim, three situations may exist: when the obligation is violated in relation to one state, when the obligation is violated with respect to a group of states and when the interests of the international community as a whole are violated. At the same time, in classical bilateral relations, only the directly injured state has the right to call to account, regardless of the seriousness of such relations, which does not prevent the third states from expressing their concern about the situation. However, in the event of a breach of obligations towards the international community as a whole, even if there is a directly affected subject of international law, the entire international community, on which behalf the United Nations has the right to claim, has the right to appeal.